2014
DOI: 10.1371/journal.pone.0112188
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism of Podocyte Involvement Is Related to Podocyte Injury in Females with Fabry Disease

Abstract: BackgroundFabry disease. an X-linked deficiency of α-galactosidase A coded by the GLA gene, leads to intracellular globotriaosylceramide (GL-3) accumulation. Although less common than in males, chronic kidney disease, occurs in ∼15% of females. Recent studies highlight the importance of podocyte injury in Fabry nephropathy development and progression. We hypothesized that the greater the % of podocytes with active wild-type GLA gene (due to X-inactivation of the mutant copy) the less is the overall podocyte in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…This is assumed to be caused by disease modifiers or in the case of women, skewed X inactivation. [7][8][9] As an alternative, plasma ly-soGb3 concentrations are a valuable tool in the classification of FD. 4,24 In line with earlier findings, 4 lysoGb3 concentrations can, indeed, be used to differentiate between phenotypes in men with FD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is assumed to be caused by disease modifiers or in the case of women, skewed X inactivation. [7][8][9] As an alternative, plasma ly-soGb3 concentrations are a valuable tool in the classification of FD. 4,24 In line with earlier findings, 4 lysoGb3 concentrations can, indeed, be used to differentiate between phenotypes in men with FD.…”
Section: Discussionmentioning
confidence: 99%
“…6 It is hypothesized that skewed X inactivation underlies the variability of the phenotype in women. [7][8][9] Treatment of FD consists of enzyme replacement therapy (ERT) and adjunctive treatment, including ACE inhibitors or angiotensin receptor blockers, antiplatelet drugs, and analgesics. Studies have shown that ERT can delay but not always prevent some of the clinical complications of the disease.…”
mentioning
confidence: 99%
“…This need is even greater in female patients, where heterogeneity in phenotype severity is even greater, perhaps in part, related to mosaicism of podocyte involvement. [27] In another study, Trimarchi et al . found increased podocyturia in Fabry patients, but with no correlation between urine podocyte density and either proteinuria or eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism of kidney involvement, probably due to the random X-inactivation, may play a pivotal role on the heterogeneous histologic findings of Fabry nephropathy in female patients [37]. The variable agreement between the podocyte vacuolization score, observed by light microscopy, and that of podocyte inclusion, observed by semi-thin slicing, reinforces the importance of both methods for evaluating podocyte deposits.…”
Section: Discussionmentioning
confidence: 94%